Spectroscopic Study of Phytosynthesized Ag Nanoparticles and Their Activity as SERS Substrate - Volodymyr Dzhagan; Oleksandr Smirnov; Mariia Kovalenko; Nazar Mazur; Oleksandr Hreshchuk; Nataliya Taran; Svitlana Plokhovska; Yaroslav Pirko; Alla Yemets; Volodymyr Yukhymchuk; Dietrich R. T. Zahn (Chemosensors, 2022)
The affordable and scalable synthesis of noble metal nanoparticles that are biocompatible without additional functionalization steps has been a growing field of research, stimulated by numerous prospective applications of these NPs. In the case of phytosynthesized or biogenic noble metal NPs, the mechanism of NP stabilization by biomolecules contained in each particular plant extract or living organism determines the possible applications of these NPs. In this work, we investigated Ag NPs synthesized in water with plant extracts of common toothwort (Lathraea squamaria) and two species of pepper (Capsicum annuum and Capsicum chinense). From FTIR and XPS, we drew conclusions about the composition of the functional groups and molecules that stabilize NPs in each extract, such as polysaccharide compounds (pectins, cellulose, glycosides and phenolic acids). Distinct characteristic IR features of amide I and amide II proteins were observed, which are common in plant extracts, while features of amide III were not distinctly observed in our extracts. A Raman spectroscopy study revealed weak own-SERS activity of the biomolecules of the extract and high efficiency of the NPs in the enhancement of “external” analytes, such as dyes and antibodies. This is the first report of the efficient SERS application of phytosynthesized Ag NPs.